Associations of BMI and its fat-free and fat components with blood lipids in children: Project HeartBeat!. (April 2011) - Dai, Shifan; Eissa, Mona A; Steffen, Lyn M; Fulton, Janet E; Harrist, Ronald B; Labarthe, Darwin R
Aim: This study aimed to distinguish between the roles of the two components of BMI, the fat mass (FM) index and the fat-free mass (FFM) index, in BMI''s association with blood lipids in children and adolescents.Methods: A total of 678 children (49.1% female, 79.9% non-black), initially aged 8, 11 and 14 years, were followed at 4-month intervals for up to 4 years (1991––1995). Total cholesterol (TC), LDL-C, HDL-C and triglycerides were determined in fasting blood samples. FFM index and FM index were calculated as FFM (kg)/height (m) 2 and FM (kg)/height (m) 2, respectively. Using a multilevel linear model, repeated measurements of blood lipids were regressed on concurrent measures of BMI or its components, adjusting for age, sex and race and, in a subsample, also for physical activity, energy intake and sexual maturity.Results: Estimated regression coefficients for the relations of TC with BMI, FFM index and FM index were 1.539, -0.606 (p > 0.05) and 3.649, respectively. When FFM index and FM index were entered into the TC model simultaneously, regression coefficients were -0.855 and 3.743, respectively. An increase in BMI was related to an increase in TC; however, an equivalent increase in FM index was related to a greater increase in TC and, when FFM index was tested alone or with FM index, an increase in FFM index was related to a decrease in TC. Similar results were observed for LDL-C. FFM index and FM index were both inversely related to HDL-C and directly to triglycerides. Compared with FFM index, the equivalent increase in FM index showed a greater decrease in HDL-C.Conclusion: Greater BMI was related to adverse levels of blood lipids in children and adolescents, which was mainly attributable to BMI''s fat component. It is important to identify weight management strategies to halt the childhood obesity epidemic and subsequently prevent heart disease in adulthood.